Enhanced interfacial interaction of epoxy nanocomposites with activated graphene nanosheets. Issue 23 (5th July 2014) - Deng, Hui; Wu, Fan; Chen, Lei; Xu, Zhiwei; Liu, Liangsen; Yang, Caiyun; Mai, Wei; Cheng, Bowen
ABSTRACT The interfacial properties of epoxy nanocomposites reinforced by thermally exfoliated graphene nanosheets (TEG) and activated thermally exfoliated graphene nanosheets (a‐TEG) were compared. The specific surface area (SSA) of a‐TEG with well‐defined micro‐mesopore size distribution was 1000 m2/g, which was much higher that of TEG (550 m2/g). The interfacial interaction between a‐TEG and epoxy was stronger than that of TEG/epoxy owing to their higher SSA and pore size which was proved by dynamic mechanical analysis. As a result, the tensile strength of a‐TEG/epoxy was increased compared with that of TEG/epoxy for all concentrations. In particular, the tensile and flexural strength of a‐TEG/epoxy was increased up to 20 and 50% in comparison to that of TEG/epoxy at 0.05 wt % graphene, respectively. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 41164.